2021
DOI: 10.3390/bios11100402
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Plasmonic Biosensor Utilizing Paired Antibody and Label-Free Fe3O4 Nanoparticles for Highly Sensitive and Selective Detection of Parkinson’s α-Synuclein in Serum

Abstract: Parkinson’s disease (PD) is an acute and progressive neurodegenerative disorder, and diagnosis of the disease at its earliest stage is of paramount importance to improve the life expectancy of patients. α-Synuclein (α-syn) is a potential biomarker for the early diagnosis of PD, and there is a great need to develop a biosensing platform that precisely detects α-syn in human body fluids. Herein, we developed a surface plasmon resonance (SPR) biosensor based on the label-free iron oxide nanoparticles (Fe3O4 NPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…For DNA sensors, the detection limit was reported to be 25 ng/mL and 75 ng/mL [ 192 ]. Surface plasmonic resonance (SPR) biosensors were developed by directly depositing label-free iron oxide nanoparticles (Fe 3 O 4 NPs) together with paired antibodies to enhance the sensitivity and selectivity efficacy of biosensors in detecting α-synuclein in the serum of a sample of patients with Parkinson’s disease [ 193 ].Electrochemical glucose biosensorswere also developed with platinum nanoparticles (PtNPs) immobilized to the surface of glucose oxidase that was deposited on poly (Azure A). The sensor showed increased selectivity with a detection limit of 7.6 μMand high sensitivity towards glucose in patients’ samples, ultimately suggesting that it is a good alternative to glucose sensors when compared to existing sensors [ 194 ].…”
Section: Nanomaterials and Their Clinical Applicationmentioning
confidence: 99%
“…For DNA sensors, the detection limit was reported to be 25 ng/mL and 75 ng/mL [ 192 ]. Surface plasmonic resonance (SPR) biosensors were developed by directly depositing label-free iron oxide nanoparticles (Fe 3 O 4 NPs) together with paired antibodies to enhance the sensitivity and selectivity efficacy of biosensors in detecting α-synuclein in the serum of a sample of patients with Parkinson’s disease [ 193 ].Electrochemical glucose biosensorswere also developed with platinum nanoparticles (PtNPs) immobilized to the surface of glucose oxidase that was deposited on poly (Azure A). The sensor showed increased selectivity with a detection limit of 7.6 μMand high sensitivity towards glucose in patients’ samples, ultimately suggesting that it is a good alternative to glucose sensors when compared to existing sensors [ 194 ].…”
Section: Nanomaterials and Their Clinical Applicationmentioning
confidence: 99%
“…Recent studies indicate that the tunable optical properties of plasmonic nanoparticle assemblies make them attractive for applications in sensing, 28–31 energy conversion, 10,32 non-linear signal enhancement, 33,34 plasmon-enhanced catalysis, 35 opto-electronic devices 36,37 and theranostics. 10,38 The optical properties in such assemblies depends on the building blocks and their spatial organization. In particular, the arrangement of the plasmonic nanoparticles in a dielectric background can be used for tuning the coupled resonances of the nanoparticles and can also be used for coupling them to other photonic or plasmonic modes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising LOD and linear ranges of these devices, the main challenges of laboratory prototypesvariations and susceptibility to small modificationsremain a significant barrier to large-scale production. Mandala et al observed the detection of αSyn in dilute serum samples with a LOD of 5.6 fg/mL, with a recovery rate of 84.5–104.3% with their plasmon resonance detector . Despite the promising LOD, the material costs and fabrication requirements are extreme with high intrinsic noise.…”
Section: Introductionmentioning
confidence: 99%
“…Mandala et al observed the detection of αSyn in dilute serum samples with a LOD of 5.6 fg/mL, with a recovery rate of 84.5−104.3% with their plasmon resonance detector. 19 Despite the promising LOD, the material costs and fabrication requirements are extreme with high intrinsic noise.…”
Section: ■ Introductionmentioning
confidence: 99%